2016
DOI: 10.1055/s-0042-101165
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Meal Stimulated Plasma GIP Levels are Higher in Lean PCOS Women with FAI over 5

Abstract: Excess androgen activity might be a factor contributing to alter secretion of incretins in lean PCOS women. However it could not be ruled out that it is also possible that increased GIP levels might induce hyperandrogenemia in PCOS. An increased GIP levels may induce hyperinsulinemia and play an additive to insulin resistance role in progression to diabetes mellitus type 2 (DMT2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Milewicz et al . [ 40 ] studied the relationship between the free androgen index and basal as well as the meal-stimulated level of glucose-dependent insulinotropic peptide (GIP) in lean women affected by PCOS. They found that excess androgen activity might be a factor contributing to alteration in the secretion of incretins in lean women affected by PCOS.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Milewicz et al . [ 40 ] studied the relationship between the free androgen index and basal as well as the meal-stimulated level of glucose-dependent insulinotropic peptide (GIP) in lean women affected by PCOS. They found that excess androgen activity might be a factor contributing to alteration in the secretion of incretins in lean women affected by PCOS.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%